Rwanda Economic Update, June 2019 : Lighting Rwanda - World Bank Group (World Bank, Kigali, 2019)
The Rwanda Economic Update (REU), published twice a year, analyzes recent economic developments and prospects and policy priorities in Rwanda. It is intended for a wide audience of policymakers, business leaders, other market participants, analysts engaged in Rwanda’s economy, and civil society. The REU draws on available data reported by the Government of Rwanda and additional information collected as part of the World Bank Group’s regular economic monitoring and policy dialogue.